Particle acceleration in stochastic current sheets in stressed coronal active regions - Turkmani, R.; Cargill, P. J.; Galsgaard, K.; Vlahos, L.; Isliker, H. (Astronomy and astrophysics (Berlin), 2006)
Aims.To perform numerical experiments of particle acceleration in the complex magnetic and electric field environment of the stressed solar corona.Methods.The magnetic and electric fields are obtained from a 3-D MHD experiment that resembles a coronal loop with photospheric regions at both footpoints. Photospheric footpoint motion leads to the formation of a hierarchy of stochastic current sheets. Particles (protons and electrons) are traced within these current sheets starting from a thermal distribution using a relativistic test particle code.Results.In the corona the particles are subject to acceleration as well as deceleration, and a considerable portion of them leave the domain having received a net energy gain. Particles are accelerated to high energies in a very short time (both species can reach energies up to 100 GeV within $5 × 10^{-2} $ s for electrons and $5 × 10^{-1}$ s for protons). The final energy distribution shows that while one quarter of the particles retain their thermal distribution, the rest have been accelerated, forming a two-part power law. Accelerated particles are either trapped within electric field regions of opposite polarities, or escape the domain mainly through the footpoints. The particle dynamics are followed in detail and it is shown how this dynamic affects the time evolution of the system and the energy distribution. The scaling of these results with time and length scale is examined and the Bremstrahlung signature of X-ray photons resulting from escaping particles hitting the chromosphere is calculated and found to have a main power law part with an index $γ = - 1.8$, steeper than observed. Possible resolutions of this discrepency are discussed.